Origin of the PN molecule in star-forming regions: the enlarged sample. Issue 4 (2nd September 2019) - Fontani, F; Rivilla, V M; van der Tak, F F S; Mininni, C; Beltrán, M T; Caselli, P
ABSTRACT: Phosphorus nitride (PN) is the P-bearing species with the highest number of detections in star-forming regions. Multiline studies of the molecule have shown that the excitation temperature of PN is usually lower than the gas kinetic temperature, suggesting that PN is likely in conditions of sub-thermal excitation. We present an analysis of PN that takes the possible sub-thermal excitation conditions into account in a sample of 24 massive star-forming regions. We observed PN (2–1), (3–2), (4–3), and (6–5) with the IRAM-30m and APEX telescopes and detected PN lines in 15 of them. Together with 9 similar sources detected in PN in previous works, we have analysed the largest sample of star-forming regions to date, made of 33 sources with 24 detections in total (among which 13 are new detections). Hence, we have increased the number of star-forming regions detected in PN by more than a factor 2. Our analysis indicates that the PN lines are indeed sub-thermally excited, but well described by a single excitation temperature. We have compared line profiles and fractional abundances of PN and SiO, a typical shock tracer, and found that almost all objects detected in PN have high-velocity SiO wings. Moreover, the SiO and PN abundances with respect to H2 are correlated over several orders of magnitude, and uncorrelated with gas temperature. This clearly shows that the production of PN is strongly linked to the presence of shocked gas, and rules out alternative scenarios based on thermal evaporation from iced grain mantles.